Pressure on a Living Room Table: A Design and Simulation Utilizing the Finite Difference Method - Hasan, Fauzi; Mardawani, Nafidz Aditya; Radiansyah, Muhammad Yushlih Fariza; Sarwani, Chamid Rosid (Department of Industrial Engineering, Universitas Jenderal Soedirman., 2023)
Computer-aided engineering (CAE) enables engineers to virtually create, analyze, and simulate items prior to their physical production. When designing furniture, such as tables, it is essential to integrate beauty with durability in order to withstand the rigors of daily use. The inclusion of pressure simulation is crucial for guaranteeing the dependability of this product. The objective of this project is to utilize SolidWorks software and a CAE methodology to develop an ideal design for a living room table. Stress simulations are employed to examine the performance of the table under various load situations and detect any design flaws that require rectification. The simulation findings indicate that the teak wood living room table undergoes deformation as a result of pressure surpassing the material's strength threshold. Nevertheless, by providing support, the amount of distortion can be minimized. Replacing the wooden material of the living room table with Aluminum Alloy 6033-0 mitigates the occurrence of deformation effects.